ANTIHYPERTENSIVE DRUG WITHDRAWAL SYNDROME - Abduraxmonova Zamira Ergashboevna; Abdukahorova Rukhshona Nodirovna (PEDAGOGS, 2024)
Abstract: Adverse drug reactions are common and pose a serious health problem, limiting treatment options, causing compliance issues, and even leading to therapy discontinuation. Hypertension is a chronic disease that is regarded as a major risk factor for cardiovascular disease. To achieve a target blood pressure in an individual patient, a wide range of anti-hypertensive agents are available as single or combination therapy, whereas combination therapy increases the risk of developing Adverse Drug Reaction. Hypertensive patients frequently have coexisting disease conditions such as hyperlipidemia, impaired glucose metabolism, and renal impairment, which increase the risk of Cardio Vascular morbidity and mortality. When treating hypertensive patients, comprehensive management of both hypertension and concomitant Cardio Vascular Disease risk factors is essential. Some of the rare and serious Adverse Drug Reactions that occurred in patients treated with these drugs included beta-blockers causing psoriasis, calcium channel blockers causing gingival hyperplasia, peripheral oedema, Angiotensin Converting Enzyme inhibitors causing ankle oedema, and thiazide diuretics causing hyponatremia and hyperglycemia. Asymptomatic hypertension is more common and necessitates lifelong treatment with antihypertensive agents, predisposing to Adverse Drug Events. In order to improve treatment outcomes and reduce morbidity and mortality associated with adverse drug reactions, healthcare professionals must monitor adverse drug reactions in patients taking antihypertensive drugs.